RTI and Mass Media: RTI as a Feeder for News - Arunkumar, R; Radha, B (Journal of Advanced Research in Journalism & Mass Communication, 2018)
Right to Information has had its origins in the 1990’s. The concept had undergone drastic changes and dimensions through the test of time. Although there were a plenty of states that brought about state level laws across the country, it was in the year 2005 that the law was actually formulated into effect as an Act majorly due to the efforts of the current CM of Delhi Shri. Arvind Kejriwal. RTI has had also been subject of intense discussion and deliberations across academia, policy makers and bureaucrats for a large period of time. Despite restraints on certain information not accessible and obtainable for the people at all times, this Act is beneficial for a large populace. The current research paper looks at information obtained from RTI by various persons becoming news articles of much importance by analysing the RTI petitions filed by various people. The study employs quantitative research approaches in the form of surveys. How to cite this article: Arunkumar R, Radha B. RTI and Mass Media: RTI as a Feeder for News. J Adv Res Jour Mass Comm 2018; 5(4): 136-138. DOI: https://doi.org/10.24321/2395.3810.201829